PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING SIMBOLIK TERHADAP KEDISIPLINAN SISWA KELAS XI SMA 1 BAE KUDUS - Mira Anisa Solechati (MEDIKONS, 2021)
Abstract: Mira Anisa Solechati NPM. 17110098: "The Effect of Group Guidance Using Symbolic Modeling Techniques on Discipline of Class XI Students of SMA 1 Bae Kudus" Thesis of Guidance and Counseling Study Program Faculty of Education, PGRI University Semarang in 2021. Advisor : Dr. Heri Saptadi Ismanto, S.Pd., M.Pd., Kons, Advisor 2 : Dr. G Rohastono Ajie, M.Pd. The background of this research is related to the discipline of class XI students of SMA 1 Bae Kudus which is shown by the behavior of students who do not understand the material presented by the teacher, feel less motivated to learn, do not collect assignments, feel not supervised by the teacher, are often late when attending lessons. The problem raised from this research is related to the discipline of class XI students of SMA 1 Bae Kudus. The purpose of the study was to determine the effect of group guidance with symbolic modeling techniques on the discipline of class XI students at SMA 1 Bae Kudus. This type of quantitative research is in the form of a true experimental design with a pretest-posttest control group design. The population used is class XI SMA 1 Bae Kudus for the academic year 2020/2021. Samples were taken using simple random sampling taken as many as 20 students, 10 students for the experimental group and 10 students for the control group. The data in this study were obtained through a research instrument in the form of a disciplinary psychology scale. It is shown by the calculation results of post-test data analysis that the average score of the experimental group increased from 1306 to 1347 after the treatment was carried out. The level of student discipline who was not given group guidance treatment with symbolic modeling techniques only had a minimal increase, from 1276 to 1301. The t-count value was 2.391 with a 5% significance level of 2.228. From before treatment was carried out it was 1306 while after treatment it was 1347, meaning that there was an increase of 41 points. Therefore, it can be